Field screening technique for peanut stem necrosis disease using Parthenium hysterophorus infector border and impact of disease on yield - Vemana, K; Venkateswarlu, N C; Rajesh, A P; Naik, K S S (Indian Journal of Plant Protection, 2020)
Among different viral diseases infecting groundnut, peanut stem necrosis disease (PSND) caused by Tobacco streak virus (TSV) is negatively impacting the yield of groundnut. Efficient field screening technique with high disease pressure of PSND is lacking to screen large number of groundnut genotypes under field conditions. TSV is pollen-borne virus as it spreads through pollen from crop and weed plants. Parthenium hysterophorus is an exotic and obnoxoius weed and it is symptomless carrier for TSV as it spreads TSV through its pollen. Parthenium was used as infector border by sowing around the screening block one month prior to groundnut sowing. It facilitates exposure of young groundnut plants to pollen of Parthenium through thrips and high disease pressure was developed. Two sets each of 62 groundnut genotypes comprising spanish and virginia were sown separately with and without infector border in randomized block design. High disease pressure of PSND was developed in the plot where Parthenium infector border was used and it ranged from 61.9-96.4 % among different genotypes at 90 days after sowing (DAS) against 5.6-22.9 % under natural conditions (without infector border). Among different genotypes, yield/ha ranged from 0.0 to 607 kg/ha using infector border against 256 to 2994 kg/ha under natural conditions. The genotype NRCG2976 recorded minimum incidence of PSND and thrips damage with and without infector border and Kadiri 7 bold recorded maximum yield in both conditions. Field screening technique helps to save time and energy in screening large number of genotypes before proceeding to artificial sap inoculation under glass house conditions.